Accuracy assessment of atmospheric correction algorithms using sunphotometers (AERONET), LIDAR system and in-situ spectroradiometers - Themistocleous, Kyriacos; Hadjimitsis, Diofantos G.; Retalis, Adrianos (My University, 2010)
Atmospheric correction is still considered as the most important part of pre-processing of satellite remotely sensed images. The accuracy assessment of the existing atmospheric correction must be monitored on a systematic basis since the user must be aware about the effectiveness of each algorithm intended for specific application. Indeed this study integrates the following measurements coincided with the satellite overpass (ASTER and Landsat TM/ETM+) in order to assess the accuracy of the most widely used atmospheric correction algorithms (such as darkest pixel, atmospheric modelling, ATCOR, 6S code etc.): spectroradiometric measurements of suitable calibration targets using GER1500 or SVC HR-1024 field spectro-radiometers, MICROTOPS hand held sun-photometers, LIDAR backscattering system, CIMEL sun photometer (Cyprus University of Technology recently joined with AERONET)
Keywords: Accuracy assessment; AERONET; AOT; Atmospheric correction; Field spectroscopy; Lidar; Sun-photometer